Insights into taxonomy and phylogenetic relationships of eleven Aristolochia species based on chloroplast genome - Bai, Xuanjiao; Wang, Gang; Ren, Ying; Su, Yuying; Han, Jinping (Frontiers in Plant Science, 2023)
The Aristolochia, as an important genus comprised of over 400 species, has attracted much interest because of its unique chemical and pharmacological properties. However, the intrageneric taxonomy and species identification within Aristolochia have long been difficult because of the complexity of their morphological variations and lack of high-resolution molecular markers. In this study, we sampled 11 species of Aristolochia collected from distinct habitats in China, and sequenced their complete chloroplast (cp) genomes. The 11 cp genomes of Aristolochia ranged in size from 159,375bp (A. tagala) to 160,626 bp (A. tubiflora), each containing a large single-copy (LSC) region (88,914-90,251 bp), a small single-copy (SSC) region (19,311-19,917 bp), and a pair of inverted repeats (IR) (25,175-25,698 bp). These cp genomes contained 130-131 genes each, including 85 protein-coding genes (CDS), 8 ribosomal RNA genes, and 37-38 transfer RNA genes. In addition, the four types of repeats (forward, palindromic, reverse, and complement repeats) were examined in Aristolochia species. A. littoralis had the highest number of repeats (168), while A. tagala had the lowest number (42). The total number of simple sequence repeats (SSRs) is at least 99 in A. kwangsiensis, and, at most, 161 in A. gigantea. Interestingly, we detected eleven highly mutational hotspot regions, including six gene regions (clpP, matK, ndhF, psbT, rps16, trnK-UUU) and five intergenic spacer regions (ccsA-ndhD, psbZ-trnG-GCC, rpl33-rps18, rps16-trnQ-UUG, trnS-GCU-trnG-UCC). The phylogenetic analysis based on the 72 protein-coding genes showed that 11 Aristolochia species were divided into two clades which strongly supported the generic segregates of the subgenus Aristolochia and Siphisia. This research will provide the basis for the classification, identification, and phylogeny of medicinal plants of Aristolochiaceae.